Energy requirements for growth in the Yorkshire terrier. (24th May 2017) - Alexander, Janet E.; Colyer, Alison; Morris, Penelope J.
Abstract: The 2006 National Research Council (NRC) equation calculating puppy energy requirements does not account for reported breed differences in growth pattern. Energy requirements of toy breed puppies are unknown and it is unclear whether feeding guidelines should differ between breeds. Energy requirements of Yorkshire terrier (YT) puppies were observed over their first year of life and compared with those predicted by the NRC and those previously observed in large (Labrador retriever) and medium (miniature Schnauzer; MS) breed puppies. Twenty-two puppies (from eight litters) were offered complete and balanced diets to maintain ideal body condition score (BCS). Energy intake, body weight and BCS were recorded from 10 to 52 weeks of age. Every 12 weeks, health was monitored by veterinary examination, routine haematology and plasma biochemistry. Puppies remained clinically healthy with normal skeletal development throughout. After analysis by linear mixed models it was observed that the NRC equation overestimates YT energy requirements between 10 and 20 weeks of age by up to 324·3 (95 % CI 390·4, 258·2) kJ/kg 0·75 . Energy intake was lower ( P  < 0·05) in YT than Labradors until 29 weeks by up to 376·6 (95 % CI 477·4, 275·3) kJ/kg 0·75 and lower than MS between 16 and 25 weeks by up to 216·3 (95 % CI 313·0, 119·7) kJ/kg 0·75 ( P  < 0·05). Data indicate differences in toy, medium and large breed energy requirements for growth. The NRC equation for puppy energy requirements overestimated the requirements of this YT population, suggesting the need for breed-specific feeding guides for growth to avoid overfeeding.